Confinement of polysulfides within bi-functional metal–organic frameworks for high performance lithium–sulfur batteries. Issue 6 (11th January 2018) - Hong, Xu-Jia; Tan, Tian-Xiong; Guo, Yu-Kai; Tang, Xue-Ying; Wang, Jian-Yi; Qin, Wei; Cai, Yue-Peng
Abstract : Cu-MOF with the dual functional binding sites is a very powerful MOF host for the inclusion of sulfur and polysulfides, demonstrating the best performance among all reported S@MOF composite cathode materials so far. Abstract : A lithium–sulfur (Li–S) battery is regarded as the most promising candidate for next generation energy storage systems, because of its high theoretical specific capacity (1675 mA h g −1 ) and specific energy (2500 W h kg −1 ), as well as the abundance, low cost and environmental benignity of sulfur. However, the soluble polysulfides Li2 S x (4 ≤ x ≤ 8) produced during the discharge process can cause the so-called "shuttle effect" and lead to low coulombic efficiency and rapid capacity fading of the batteries, which seriously restrict their practical application. Using porous materials as hosts to immobilize the polysulfides is proved to be an effective strategy. In this article, a dual functional cage-like metal–organic framework (Cu-MOF), Cu-TDPAT, combining the Lewis basic sites from the nitrogen atoms of the ligand H6 TDPAT with the Lewis acidic sites from Cu(ii ) open metal sites (OMSs), was employed as the sulfur host in a Li–S battery for lithium ions and polysulfide anions (S x 2− ). In addition, the size of nano-Cu-TDPAT was also optimized by microwave synthesis to reduce the internal resistance of the batteries. The electrochemical test results showed that the optimized Cu-TDPAT material can efficiently confine the polysulfides within the MOF, and the resultant porous S@Cu-TDPAT composite cathode material with the size of 100 nm shows good cycling performance with a reversible capacity of about 745 mA h g −1 at 1C (1C = 1675 mA g −1 ) after 500 cycles, to the best of our knowledge, which is higher than those of all reported S@MOF cathode materials. The DFT calculation and XPS data indicate that the good cycling performance mainly results from the dual functional binding sites (that is, Lewis acid and base sites) in nanoporous Cu-TDPAT, providing the comprehensive and robust interaction with the polysulfides to overcome their dissolution and diffusion into the electrolyte. Clearly, our work provides a good example of designing MOFs with suitable interaction sites for the polysulfides to achieve S@MOF cathode materials with excellent cycling performance by multiple synergistic effects between nanoporous host MOFs and the polysulfides.